Mirror for humanity : - Kottak, Conrad Phillip (McGraw-Hill Higher Education, 2005)
This concise, up-to-date, inexpensive introduction to cultural anthropology carefully balances coverage of core topics with contemporary changes in the field. Since no single or monolithic theoretical perspective orients this book, instructors with a wide range of views and approaches can use it effectively.